ANALISIS STABILITAS STRUKTUR PELAT DENGAN SOLUSI DERET FOURIER DAN FINITE DIFFERENCE - Saloma, Saloma; Dolu, Anwar (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2007)
Differential Equation of Slab is manifestation from mathematic model that refers physics fenomens from slab flexible, which is decreased by asumstions that have related with material characteristics such as elastic linear, homogen, isotropic and others physics attitude. This differential equation solution with finite difference and Fourier Series is changed determines Differential Equation of Slab to trigonometric functions (sinus and cosinus), addition all trigonometric funcfion produce analytic solution from Differential Equation of Slab.